Analysis of solar PV glare in airport environment: Potential solutions - Sreenath, S.; Sudhakar, K.; Ahmad Fitri, Yusop; Cuce, Erdem; Solomin, Evgeny (Elsevier B.V., 2019)
Solar PV plants are being installed in many airports around the globe. Reflection from the solar PV arrays is a big concern for airport stakeholders. This paper aims to assess the glare occurrence and its impact from the proposed solar PV plant installed in an airport. The prediction of glare is carried out with the help of computational software for a randomly selected area within the boundary of Kuantan airport, Malaysia. The selected zone is not suitable for solar installations as per FAA's glare policy. In the selected area (Apv), the duration of glare on ATCT from solar modules installed is 6778 min (green and yellow glare). Also, the flight path is free from any kind of glare occurrence. Glare occurs between March to mid-October, mostly from 7.00 a.m. to 8.00 a.m. Green and Yellow glare last up to 10 min and 30 min respectively in a year. In this regard, remedial steps for mitigating possible glare are discussed. Glare prediction helps in the early adoption of suitable remedial measures against glare hazard.